Sustainable Engagement with Indigenous Settlements in Prohibited Areas: Case Study of Karen Tribe Villagers in the Kaengkrachan Forest Complex, Thailand - Tarnrawee Ngamsiriudom; Terdsak Tachakitkachorn; Monsinee Attavanich; Chalumpon Thawanaphong; Piyathida Saikhun (Nakhara Journal of Environmental Design and Planning, 2021)
Cultural Housing Network Project under collaboration by The Department of National Park, Pidthong Foundation and Chulalongkorn University has been initiated as a social engagement to solve conflicts between the Department of National Park and Primitive Karen tribe villagers in this prohibited area. Treatment bamboo for multi-utilizing and pre-establishing of village working group for cultural promotion has been raised as the key success factors, in parallel with trial and error activity for natural and cultural tourism. These were engaged to reconstruct the village pride of their local wisdom and widen up the job opportunity for their next generation, under restricted regulation by the Department of National Park and long-term distrustful conflicts between both sides. Chulalongkorn University and Pidthong Foundation, as the academic and NPO sectors, have to retain their neutral stances by following up a consensus roadmap of sustainable engagement plan, to counter measurement with any unexpected emerging pressures from both sides.
Keywords: Southeast Asian Sociopolitical Studies; Cambodian History and Society; Cultural Heritage Management and Preservation